2017
DOI: 10.1167/iovs.17-22389
|View full text |Cite
|
Sign up to set email alerts
|

Fixational Saccades and Their Relation to Fixation Instability in Strabismic Monkeys

Abstract: PurposeTo evaluate the contribution of fixational saccades toward fixation instability in strabismic monkeys.MethodsBinocular eye movements were measured as six experimental monkeys (five strabismic monkeys and one monkey with downbeat nystagmus) and one normal monkey fixated targets of two shapes (Optotype, Disk) and two sizes (0.5°, 2°) during monocular and binocular viewing. Fixational saccades were detected using an unsupervised clustering algorithm.ResultsWhen compared with the normal monkey, amplitude an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 34 publications
3
12
0
Order By: Relevance
“…They also show responses during quick-phases of nystagmus whose amplitudes overlap that of microsaccades. 50 We therefore suggest that misalignment-related cells are the same population of previously described fixation/microsaccade cells or perhaps constitute a subset that also carries information about strabismus angle.…”
Section: Are the Vergence And Misalignment-related Cells Distinct Frosupporting
confidence: 53%
“…They also show responses during quick-phases of nystagmus whose amplitudes overlap that of microsaccades. 50 We therefore suggest that misalignment-related cells are the same population of previously described fixation/microsaccade cells or perhaps constitute a subset that also carries information about strabismus angle.…”
Section: Are the Vergence And Misalignment-related Cells Distinct Frosupporting
confidence: 53%
“…BCEA as a measure has several limitations including assumption of normality of the underlying position distributions; thus, the values can be affected by the presence of outliers (Castet & Crossland, 2012). Because BCEA is a measure of dispersion of eye position, it takes into account both the fast and slow eye movements and does not identify the presence of FMN (Upadhyaya et al, 2017). FMN is a characteristic oculomotor deficit suggestive of disruption of binocularity in the first six months of life.…”
Section: Introductionmentioning
confidence: 99%
“…Animal model studies have shown that disruption of binocularity during infancy is invariably associated with gaze instabilities, most often FMNS 6 , 58 . Tychsen and colleagues have shown in experiments that the prevalence and severity of FMNS increases with the longer duration of binocular decorrelation with 100% prevalence of FMNS in primates who are exposed to periods of binocular decorrelation that is equivalent to 3 months in humans.…”
Section: Discussionmentioning
confidence: 99%